Immunogenicity of RV1 and RV5 vaccines administered in standard and interchangeable mixed schedules: a randomized, double-blind, non-inferiority clinical trial in Mexican infants - Macías-Parra, Mercedes; Vidal-Vázquez, Patricia; Reyna-Figueroa, Jesús; Rodríguez-Weber, Miguel Ángel; Moreno-Macías, Hortensia; Hernández-Benavides, Inés; Fortes-Gutiérrez, Sofía; Richardson, Vesta Louise; Vázquez-Cárdenas, Paola (Frontiers in Public Health, 2024)
Introduction: Rotavirus-associated diarrheal diseases significantly burden healthcare systems, particularly affecting infants under five years. Both Rotarix TM (RV1) and RotaTeq TM (RV5) vaccines have been effective but have distinct application schedules and limited interchangeability data. This study aims to provide evidence on the immunogenicity, reactogenicity, and safety of mixed RV1-RV5 schedules compared to their standard counterparts.Methods: This randomized, double-blind study evaluated the non-inferiority in terms of immunogenicity of mixed rotavirus vaccine schedules compared to standard RV1 and RV5 schedules in a cohort of 1,498 healthy infants aged 6 to 10 weeks. Participants were randomly assigned to one of seven groups receiving various combinations of RV1, and RV5. Standard RV1 and RV5 schedules served as controls of immunogenicity, reactogenicity, and safety analysis. IgA antibody levels were measured from blood samples collected before the first dose and one month after the third dose. Noninferiority was concluded if the reduction in seroresponse rate in the mixed schemes, compared to the standard highest responding scheme, did not exceed the non-inferiority margin of -0.10. Reactogenicity traits and adverse events were monitored for 30 days after each vaccination and analyzed on the entire cohort.Results: Out of the initial cohort, 1,365 infants completed the study. Immunogenicity analysis included 1,014 infants, considering IgA antibody titers ≥20 U/mL as seropositive. Mixed vaccine schedules demonstrated non-inferiority to standard schedules, with no significant differences in immunogenic response. Safety profiles were comparable across all groups, with no increased incidence of serious adverse events or intussusception.The study confirms that mixed rotavirus vaccine schedules are non-inferior to standard RV1 and RV5 regimens in terms of immunogenicity and safety. This finding supports the flexibility of rotavirus vaccination strategies, particularly in contexts of vaccine shortage or logistic constraints.These results contribute to the global effort to optimize rotavirus vaccination programs for broader and more effective pediatric coverage.